Bone repair using mineral trioxide aggregate combined to a material carrier, associated or not with calcium hydroxide in bone defects - do Nascimento, Cassio; Mardegan Issa, Joao Paulo; Mizusaki Iyomasa, M.; Hallak Regalo, Simone Cecilio; Siessere, Selma; Pitol, Dimitrius Leonardo; Wolga, Nilce de Oliveira; Pedrazzi, Vinicius (Pergamon-Elsevier B.V. Ltd, 2008)
Mineral trioxide aggregate (MTA) is a powder aggregate containing mineral oxides with a good biological action and may facilitate the regeneration of the periodontal ligament and formation of bone. Calcium hydroxide demonstrates antibacterial properties, enhances tissue dissolution, and induces bone formation. The objective of this study was to evaluate the MTA in the bone healing process and verify if the calcium hydroxide P.A. can improve and accelerate this process. It was used forty rnale Wistar rats, which were divided into two groups, considering or not the use of calcium hydroxide P.A. solution before treatment. Thus, each one of these groups was divided in four groups with five animals each, according to the treatment and the defect filled by: animal's coagulum, monoolein gel, MTA in aqueous solution, and MTA combined with monoolein gel. After 10 days, the animals were perfused and the right hemimandibles removed for histological analysis. Statistical analysis of the data showed significant difference between all analyzed groups when it was made comparisons using or not calcium hydroxide P.A. (p < 0.0001). There was found statistical difference between the groups that was inserted or not MTA, independently the calcium hydroxide application (p < 0.05). Results showed that the MTA used was able to induce bone regeneration and had its action optimized when combined to calcium hydroxide P.A. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: calcium hydroxide; MTA; periapical bone defect; histology